A IMPORT NCIA DO CONTATO COM A ODONTOPEDIATRIA PARA O DESENVOLVIMENTO BUCAL INFANTIL (REMUNOM, 2024)
In current Brazilian times, the consequence of the lack of contact with pediatric dentistry during childhood is noticeable. Such a problem appears as an obstacle to the child's oral development, since the lack of contact with the dentist during childhood can develop several problems for the child's oral and general health. Thus, the proposed study carried out a literature review, with the aim of identifying, through a literature review on the subject, the importance of contact with pediatric dentistry for children's oral development. Likewise, it became necessary to emphasize the particularities of child oral development, since the pediatric dentist has mastery in dealing with them. In addition, the lack of access to dental care, due to socioeconomic issues, stood out as the main problem of the imbroglio. Finally, it is notable that the pediatric dentist has mastery in dealing with children.